Effect of white oats, black oats, ryegrass and wheat cultivation on agronomic soybean characteristics - dos Santos, Henrique Pereira (Pesquisa Agropecuaria Brasileira, 1991)
During four years nine cropping systems were evaluated at the Centro Nacional de Pesquisa de Trigo (National Wheat Research Center), Passo Fundo, Brazil, in relation to yield and other agronomic characteristics of soybean. Soybean was cultivated in succession to different winter crops (black oats, white oats, ryegrass, and wheat), distributed in several crop rotation systems. The winter crops were established under conventional tillage and the Summer crop was direct-drilled. Plots of 18 m2 and a randomized blocks design with three replications were used. Soybean grown after white oats, black oats, ryegrass and wheat showed no significant differences for yield, yield components and 1,000 grain weight. Final stand, plant height and insertion of the first pods were influenced by the preceding winter crops. All characteristics studied were influenced by the year factor.